The Impact of International Human Rights Law on Digital Privacy in the Era of Mass Surveillance (International Forum of Researchers and Lecturers, 2025)
The rapid advancement of digital technology has led to widespread mass surveillance, raising concerns about the protection of individual privacy. International human rights law plays a crucial role in balancing national security interests with the right to digital privacy. This study examines the impact of international human rights frameworks, such as the Universal Declaration of Human Rights (UDHR) and the International Covenant on Civil and Political Rights (ICCPR), in safeguarding digital privacy amid increasing government surveillance. Using a qualitative approach, the research analyzes key legal principles, court rulings, and policy responses from different jurisdictions. The findings indicate that while international legal instruments provide a foundation for digital privacy protection, enforcement remains inconsistent due to varying national implementations and technological challenges. The study underscores the need for stronger legal mechanisms and international cooperation to ensure the effective protection of digital privacy rights in the digital age.